Occupational silica exposure in an Australian systemic sclerosis cohort. (10th September 2020) - Patel, Shreeya; Morrisroe, Kathleen; Proudman, Susanna; Hansen, Dylan; Sahhar, Joanne; Sim, Malcolm R; Ngian, Gene-Siew; Walker, Jenny; Strickland, Gemma; Wilson, Michelle; Ferdowsi, Nava; Major, Gabor; et al.
Abstract: Objective: To determine the frequency of self-reported occupational exposure to silica in SSc patients enrolled in the Australian Scleroderma Cohort Study, and to compare the disease characteristics of the silica-exposed patients with those of the non-exposed patients. Method: Data collected over a 12-year period from 1670 SSc patients were analysed. We compared the demographic and clinical characteristics of those who reported occupational silica exposure with those who did not. A subgroup analysis of male patients was performed, as well as a multivariable analysis of correlates of silica exposure. Results: Overall, 126 (7.5%) of the cohort reported occupational silica exposure. These individuals were more likely to be male (73 of 231, i.e. 31.6% males exposed) and to have worked in mining and construction industries. Those who reported silica exposure were younger at the onset of SSc skin involvement [odds ratio (OR) 0.9, P  = 0.02], of male gender (OR 14.9, P  < 0.001), have joint contractures (OR 1.8, P  = 0.05) and have higher physical disability as defined by scleroderma HAQ (OR 1.4, P  = 0.01). Conclusion: The highest percentage of silica exposure was found in males. These patients were more likely to have the presence of certain clinical manifestations and Scl-70 antibody, which is known to confer a poor prognosis. These findings support the association between occupational silica exposure and the subsequent development of SSc. Further investigation is required to describe the range of clinical manifestations and disease course, including prognosis and treatment response, in those diagnosed with occupationally induced SSc compared with idiopathic SSc.